Evaluating Soybean Cultivars for Forage Yield and Nutritive Values. (7th May 2021) - Thompson, Serena; Koebernick, Jenny; Carrell, Russell C; Cole, Madison; Dillard, S Leanne L
Abstract: Alfalfa ( Medicago sativa ) and perennial peanut ( Arachis glabrata ) are frequently utilized by equine producers in the Southeast. However, challenges related to their production have producers searching for alternative legume options. In 2019 and 2020, five soybean cultivars, "Tower of Leaves, " "Stonewall, " "Laredo, " "AG79X9, " and "AG64X8, " were evaluated for yield and nutritive value. Soybeans were grown at two row spacings (36 and 71 cm), two locations (Central and South Alabama), and harvested at three heights (10, 15, and 20 cm; HH). Forages were harvested using a plot harvester, dried at 55°C, and ground to 1 mm. Forage quality was determined using a NIRS, with verification by wet chemistry analyses. The study was a randomized, complete block design (n = 4) and statistical analysis was carried out using PROC Glimmix of SAS version 9.4 (SAS Inst., - Cary, NC). Forage yields were greatest in "Stonewall" and "Tower of Leaves, " and lowest in "Laredo" (2, 074, 1, 978, and 1, 348 kg/ha, respectively). Across years, HH and forage cultivar had a significant effect on yield (P < 0.0001). As expected, yield increased as HH decreased (P < 0.0001). In 2019, crude protein (CP) was affected by HH (P < 0.0001), with 10 cm having lower CP than 15 and 20 cm (14 vs 16%, respectively; P < 0.0001). Neutral detergent fiber (NDF), acid detergent fiber (ADF), and total digestible nutrients (TDN) were affected (P < 0.01) by HH and variety. "Stonewall" had the lowest NDF (30.84%) and ADF (29.27%; P < 0.01). "Stonewall" and "AG79X9" had the greatest TDN (74 and 73%, respectively; P < 0.01). The cultivar "Stonewall" shows promise as a forage, with greater yields and moderate forage nutritive value compared with the other cultivars tested. Further research is needed to evaluate "Stonewall" in mixtures with other warm-season annual forages.